2011
DOI: 10.1258/ebm.2011.011090
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy in a rat model of hyperoxaluria: the antioxidant effects of quercetin involve serum paraoxonase 1 activation

Abstract: Serum paraoxonase 1 (PON1) has been reported to be an important contributor to the antioxidant and anti-inflammatory activities of HDL, avoiding LDL oxidation. The activity of this enzyme is reduced in patients with renal insufficiency, caused by elevated oxidative stress and disturbances of apolipoprotein metabolism. Therapeutic utilization of antioxidants to control renal oxidative stress may be an effective therapy in renal protection. The aim was to investigate the protective effects of several antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…The formation of a metal sulfhydryl complex decreases the activities of such enzymes . The decrease in PON1 activity by cisplatin treatment is in agreement with the study of Amengual‐Cladera et al., . PON1 has free thiol residues that are essential for its activity .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The formation of a metal sulfhydryl complex decreases the activities of such enzymes . The decrease in PON1 activity by cisplatin treatment is in agreement with the study of Amengual‐Cladera et al., . PON1 has free thiol residues that are essential for its activity .…”
Section: Discussionsupporting
confidence: 90%
“…PON1 exerts paraoxonase and arylesterase activities, since the enzyme hydrolyzes both paraoxon and aromatic esters . The activity of PON1 is reduced in renal insufficiency caused by elevated oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…The main chemical components in L. christinae are flavonoids (37). As for the flavonoids in L. christinae, quercetin is relatively abundant (37) and has been found to have antioxidant activity in the previous study (38). However, it was still not clear until now that quercetin is the main hepatoprotective chemical compound of L. christinae.…”
Section: Discussionmentioning
confidence: 97%
“…In a study with using the model of renal failure induced by ethylene glycol, it was reported that treatment impaired kidney composition, increased oxidative damage, and decreased serum paraoxonase and arylesterase activities [64]. Quercetin and cathechins enhanced antioxidant defenses—superoxide dismutase and PON1 activities, reducing oxidative damage suggesting that PON1 mediates the protective effects of flavonoids against kidney damage by oxidative stress [64].…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Quercetin and cathechins enhanced antioxidant defenses—superoxide dismutase and PON1 activities, reducing oxidative damage suggesting that PON1 mediates the protective effects of flavonoids against kidney damage by oxidative stress [64]. …”
Section: Intervention Studiesmentioning
confidence: 99%